Report and proceedings of the Symposium on aquaculture development - partnership between science and producer aáociations. Wierzba, Poland, 26-29 May 2004 held in connection with the European Inland fishery advisory commiáion twenty-third seáion Wierzba, Poland, 26 May - 2 Jun 2004 - FAO, Roma (Italia) (Roma (Italia), 2006)
Sumario (En)
Ilus.; 109 ref.
Keywords: ACUICULTURA; DESARROLLO PESQUERO; ASISTENCIA TECNICA; ORDENACION DE RECURSOS; ORGANIZACIONES INTERNACIONALES; PESCA; INVESTIGACION; TRANSFERENCIA DE TECNOLOGIA; DISTRIBUCION GEOGRAFICA; SIMPOSIO